PECULIARITIES OF REAGENT PROCESSING OF THE CLOSED CIRCULATING SYSTEMS WITH UNITS OF AIR COOLING - F. P. Gamidov; I. V. Kotov (Литьë и металлургия)
The peculiarities of reagent processing of closed circulating systems with apparatus of air cooling are examined.